THE MAIN ASPECTS OF THE PATHOGENESIS OF GASTRODUODENOPATHY ASSOCIATED WITH NON-STEROIDAL ANTI-INFLAMMATORY DRUGS IN PATIENTS WITH OSTEOARTHRITIS - Гончарук, Л.М.; Піддубна, А.А.; Андрущак, М.О.; Семко, Г.; Кочурка, Л. (SWorldJournal, 2023)
The largest group of users of non-steroidal anti-inflammatory drugs are patients with rheumatoid arthritis and osteoarthritis. Nonsteroidal gastropathies are diagnosed in approximately 70% of patients who systematically use these drugs. The article provi